Penilaian Tata Kelola dan Manajemen Layanan Teknologi Informasi dengan Cobit 2019 dan ITIL 4 - Erika Nachrowi; Yani Nurhadryani; Heru Sukoco (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The implementation of E-government evaluation is already a necessity to know the level of process of governance and management of service and provide improvement suggestions for quality improvement. Evaluation of the governance and management of services at the Directorate Institutional, Directorate General of Higher Education using the COBIT 2019, by measuring the capability process level based on the design factor which recommends improvement priorities in the 11 domain COBIT 2019 and the level of user satisfaction of service applications using the E-govqual model. IT capability level assessment results have 3 levels 0 processes or no existing approaches, 6 levels 1 processes or incomplete approaches, 1 level 2 process or initial approach fulfils the intent of the practice area and 1 Process level 3 or achievement of objectives is much more organized. Service Satisfaction rate measurement get 3 criteria in Quadrant A or priority improvement, 13 criteria in quadrant B or maintained, 12 criteria in quadrant C or less priority and 3 criteria in Quadrant D or less expected. Repair recommendations are compiled based on the SWOT model, referring to COBIT 2019 and ITIL 4. The results of the recommendation include increased competency of human resources and integrate services with PDDIKTI.